2010
DOI: 10.1016/j.bmc.2010.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and kinetic analysis of some phosphonate analogs of cyclophostin as inhibitors of human acetylcholinesterase

Abstract: Two new monocyclic analogs of the natural AChE inhibitor cyclophostin and two exocyclic enol phosphates were synthesized. The potencies and mechanisms of inhibition of the bicyclic and monocyclic enol phosphonates and the exocyclic enol phosphates toward human AChE are examined. One diastereoisomer of the bicyclic phosphonate exhibits an IC50 of 3 μM. Potency is only preserved when the cyclic enol phosphonate is intact and conjugated to an ester. Kinetic analysis indicates both a binding and a slow inactivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 22 publications
1
43
1
Order By: Relevance
“…As stated in the introduction, we have previously shown that cyclophostin inhibits AChE irreversibly [8]. Since the basic chemistry should be the same, we expect cyclipostin to inhibit HSL irreversibly.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…As stated in the introduction, we have previously shown that cyclophostin inhibits AChE irreversibly [8]. Since the basic chemistry should be the same, we expect cyclipostin to inhibit HSL irreversibly.…”
Section: Resultsmentioning
confidence: 84%
“…The synthesis of the monocyclic phosphonates ( 7, 8, 9a, 10a, 10b, 11a, 11b, 12a, 12b ) also followed published procedures [8, 26]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations